1969
DOI: 10.1073/pnas.63.1.191
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Methylmalonic Acidemia: Enzymatic Evidence for Two Forms of the Disease

Abstract: Abstract.-Methylmalonic acidemia is an inherited metabolic disorder thus far found in children and characterized by the excessive excretion of methylmalonate in the urine. Typically these children exhibit vomiting, lethargy, ketoacidosis, and failure to grow. Many of the patients are mentally retarded and die early in life. Two variants of this disease are known. In one, the administration of vitamin B12 will reverse or prevent these clinical findings, whereas in a second variant vitamin B12 therapy is of no v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
34
0

Year Published

1971
1971
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(35 citation statements)
references
References 9 publications
(2 reference statements)
1
34
0
Order By: Relevance
“…A theoretical exception to this rule is the failure of a polarity mutant to complement a point mutation in a distal gene of an operon or gene cluster (12,13), but such phenomena are very rare and have been observed only in bacteria and fungi. Second, the prominent biochemical differences both between the mutase apoenzyme and the Cbl mutants (1,7), and among the Cbl mutants (4,5) (1975) 3185 that these two classes reflect mutations at the same locus and that the complementation observed between them is intragenic. For instance, one step in AdoCbh synthesis could be catalyzed by an enzyme composed of two identical subunits and bound to the mitochondrial membrane.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A theoretical exception to this rule is the failure of a polarity mutant to complement a point mutation in a distal gene of an operon or gene cluster (12,13), but such phenomena are very rare and have been observed only in bacteria and fungi. Second, the prominent biochemical differences both between the mutase apoenzyme and the Cbl mutants (1,7), and among the Cbl mutants (4,5) (1975) 3185 that these two classes reflect mutations at the same locus and that the complementation observed between them is intragenic. For instance, one step in AdoCbh synthesis could be catalyzed by an enzyme composed of two identical subunits and bound to the mitochondrial membrane.…”
mentioning
confidence: 99%
“…Some patients with methylmalonicacidemia respond to administration of pharmacologic doses of vitamin B12 with decreased accumulation of methylmalonic acid and clinical improvement (7,14). Such responsive patients appear to be restricted to those with defects of Cbl metabolism.…”
mentioning
confidence: 99%
“…C succinate respectively before they are completely oxidized to C0 2 (6,32,33). Thus, it should be possible to assess the relative effect of metabolism occurring within and without the TCA cycle upon the radiorespirometry pattern by a comparison of the results obtained in studies with each pair of compounds.…”
Section: +mentioning
confidence: 99%
“…Methods that are available to you, or at least some of them, are presented in Table IV. NUCLEAR MAGNETIC RESONANCE -ODD NUCLEI 13 C, 15 N, and 33 S CAN "SEE" THE ENVIRONMENT OF THE ATOM IN A COMPLEX MOLECULE.…”
mentioning
confidence: 99%
“…In 1969 Morrow et al (1969b) measured the methylmalonyl-CoA mutase activity using liver biopsy specimens from patients with vitamin B12 responsive or unresponsive type of methylmalonic acidemia, and reported that in the case with vitamin B12 responsive type the mutase activity was restored to the normal when DBCC was added to the assay media.…”
mentioning
confidence: 99%